Detection of Phishing URLs using Bayes Net and Naïve Bayes and evaluating the risk assessment using Attributable Risk - Raj, Priya; Mittal, Meenakshi (International Journal of Computer Sciences and Engineering, 2025)
Phishing sites are manufactured or spurious URLs that are made by malignant people to imitate or imitate URLs of genuine URLs. An extensive bit of these sorts of URLs have most elevated twin to trap their casualties for tricks. Unwary Web customers may be successfully betrayed by this kind of trick. The effect is the break of data security through the exchange of private information and the losses may encounter the bad effects of financial losses and more example hacking. In this paper detection of phishing URLs is done by using Bayes net and Naïve Bayes algorithm and evaluation of risk regarding phishing URLs is done with the help of attributable risk. A training dataset of 1800 URLs (containing 1080 legitimate and 720 phished URLs) has been made to train the algorithms. Testing dataset of 720 URLs (containing 288 legitimate and 432 phished URLs) is used for making predictions using the DAG model classifier which is generated after the training of Bayes Net and Naïve Bayes Algorithm. True negative rate, True positive rate, false negative rate, false positive rate, Error rate and Accuracy are calculated after testing dataset by DAG classifier. Result shows Bayes Net has an accuracy of 71.3% and the Naïve Bayes has an accuracy of 80.5% and calculation of risk is done on the basis of attributable risk. If risk percentage for the URLs attributes is greater than 80% then risk is high, if it is between 50-80% then risk is medium and below 50% risk is low.